Population Genetics in the Human Microbiome - Garud, Nandita R.; Pollard, Katherine S. (Trends in genetics, 2020)
While the human microbiome’s structure and function have been extensively studied, its within-species genetic diversity is less well understood. However, genetic mutations in the microbiome can confer biomedically relevant traits, such as the ability to extract nutrients from food, metabolize drugs, evade antibiotics, and communicate with the host immune system. The population genetic processes by which these traits evolve are complex, in part due to interacting ecological and evolutionary forces in the microbiome. Advances in metagenomic sequencing, coupled with bioinformatics tools and population genetic models, facilitate quantification of microbiome genetic variation and inferences about how this diversity arises, evolves, and correlates with traits of both microbes and hosts. In this review, we explore the population genetic forces (mutation, recombination, drift, and selection) that shape microbiome genetic diversity within and between hosts, as well as efforts towards predictive models that leverage microbiome genetics. Genetic variation in host-associated microbiomes can be assayed in a high-throughput manner with a variety of technologies.Many bacterial species recombine extensively, although they asexually reproduce.The genetic diversity of many species within and across hosts is spatially structured.Evidence for rapid adaptation within hosts is starting to emerge.Modeling efforts are connecting microbiome genetic variants with host phenotypes, highlighting the biomedical importance of genetic variation in the microbiome.